Hubungan Risiko Kerja Berdiri Dengan Tingkat Kelelahan Kerja Pada Operator Mesin Tenun PT. Iskandar Indah Printing Textile Surakarta - KHASANAH, ISNAINI MISBAKHUL, Dr. Suwaji, M.Kes, Tri Puji Kurniawan, SKM, M. Kes (2016)
THE CORRELATION BETWEEN STANDING-UP WORK POSITION AND WORK FATIGUE LEVEL IN THE OPERATORS OF WEAVER MACHINE AT PT. ISKANDAR INDAH PRINTING TEXTILE SURAKARTA Fatigue, in fact, can influence the workers' health and can decrease the work productivity. Besides, fatigue is also able to give a significant contribution on the work accident. Therefore, it is necessary to find out the causing factors of fatigue in the workers, which are the fatigue factors. The objective of this research was to know the correlation between the standing-up position and the work fatigue level in the Operators of Weaver Machine at PT. Iskandar Indah Printing Textile Surakarta. Subjects in this research were the operators of weaver machine at PT. Iskandar Indah Printing Textile Surakarta. The technique of sampling was Proportional Random Sampling, as many as 47 respondents divided into three shifts. The measurements used to reveal the research variables were 2 kinds of measurement: (1) the measurement form of Owas method, and (2) questionnaire of subjective fatigue. The data analysis in this research used the analysis of univariat and bivariat. Based on the results of measurement on the workers' work position, most of them were in the category of low risk, they were 16 respondents (34.0%). The result of measurement on the workers' fatigue was that most of them were in the very high category, they were 22 respondents (46.8%). It could be concluded that there was a significant correlation between the risc work position and the fatigue level in which p=0.003 and r=0.041. The results showed that there was a correlation toward a positive correlation, that was the higher the risk of standing-up work position, the higher the fatigue level was. Keywords: Risc work position, Fatigue Workers.